Effect of Garlic (Allium sativum) Extract on Recovery and Conception Rate in Infectious Repeat Breeder Crossbred Cows - Bhardwaj, Anvil; Nema, SP; Mahour, SS; Chabra, Daljeet; Rajput, N; Sudarshan, K (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The study was undertaken to evaluate the therapeutic efficacy of Garlic (Allium sativum) extract in 20 infectious repeat breeder crossbred cows. Animals were divided into two groups of ten in each. The animals in first group were treated intrauterine with 30 ml 15% Garlic extract w/v dissolved in saline at 24 hrs interval for 7 days, while the animals in control group were infused with 30 ml saline for 7 days. Bacterial count in uterine flushing declined significantly (p<0.05) after treatment in Garlic group. A significant increase (p< 0.05) in total cellular count and PMNs % was found in Garlic group than in control group. An overall recovery rate of 80 vs 20 % and conception rate of 60 vs 10 % was found in Garlic treated cows over control placebo group proving its efficacy in infectious repeat breeders. buffaloes. The present study was carried out to One calf a year by cow is essential for economic viability in dairying. Repeat breeding, comprise a heterogeneous group of subfertile cows with a tune of 7.31 to 23.88 % among bovines. Though, antibiotics are quite effective in treating endometritis, but use of herbal medicines as antimicrobial and/or immunomodulator is becoming popular due to toxicity and side effects of allopathic medicines. Extract of Garlic (Kumar, 2013 and Singh, 2016) has been suggested as alternative therapy for repeat breeding cattle and evaluate the efficacy of Garlic extract I/Ut infusion in repeat breeding crossbred cows.